Real-World Evidence in Glioblastoma: Stupp's Regimen After a Decade - Lakomy, Radek; Kazda, Tomas; Selingerova, Iveta; Poprach, Alexandr; Pospisil, Petr; Belanova, Renata; Fadrus, Pavel; Vybihal, Vaclav; Smrcka, Martin; Jancalek, Radim; Hynkova, Ludmila; Muckova, Katarina; et al. (Frontiers in Oncology, 2020)
The aim of this retrospective study is to provide real-world evidence in glioblastoma treatment and to compare overall survival after Stupp's regimen treatment today and a decade ago. A current consecutive cohort of histologically confirmed glioblastoma irradiated from 1/2014 to 12/2017 in our cancer center was compared with an already published historical control of patients treated in 1/2003-12/2009. A total of new 155 patients was analyzed, median age 60.9 years, 61% men, 58 patients (37%) underwent gross total tumor resection. Stupp's regimen was indicated in 90 patients (58%), 65 patients (42%) underwent radiotherapy alone. Median progression-free survival in Stupp's regimen cohort was 6.7 months, median OS 16.0 months and 2-year OS 30.7%. OS was longer if patients were able to finish at least three cycles of adjuvant chemotherapy (median 23.3 months and 43.9% of patients lived at two years after surgery). Rapid early progression prior to radiotherapy was a negative prognostic factor with HR 1.87 (p = 0.007). The interval between surgery and the start of radiotherapy (median 6.7 weeks) was not prognostically significant (p = 0.825). The median OS in the current cohort was about two months longer than in the historical control group treated 10 years ago (16 vs 13.8 months) using the same Stupp's regimen. Taking into account differences in patient's characteristics between current and historical cohorts, age, extent of resection and ECOG patient status adjusted HR (Stupp's regimen vs. RT alone) for OS was determined as 0.45 (p = 0.002).